Seventy-two models of large mammal connectivity across Panama: insights into a critical biogeographic linkage zone - Cushman, Samuel A.; Craighead, Kimberly A.; Yacelga, Milton; Kaszta, Zaneta M.; Wan, Ho Yi; Macdonald, David W. (Frontiers in Ecology and Evolution, 2023)
In this study we explore 72 different models of landscape connectivity for jaguars and pumas across Panama to evaluate the plausible current patterns of habitat connectivity for these and potentially other species in this critical biogeographic linkage zone. Our approach developed resistance surfaces for both big cats based on published empirical species distribution models transformed into resistance surfaces and expert-based land use resistance for jaguars and pumas. We generated source points probabilistically for each scenario based on habitat suitability. We conducted resistant kernel modeling with three different dispersal abilities to reflect uncertainty in the movement potential of the two species. We applied three transformations to the resulting connectivity surfaces to account for uncertainty about the shape of the dispersal kernel function. In combination, these factors produced 72 connectivity models, 36 for each species. We then evaluated the similarities and differences among these connectivity models, identifying several factors that drive their differences. We then produced a correlation matrix among all the pixels of each of the predicted connectivity surfaces, and we used the Mantel test to evaluate the relationship between the correlation between connectivity surfaces and different explanatory hypotheses. We found that the main differences among predicted connectivity surfaces were related to species and resistance modeling approach, with relatively little consistent difference related to dispersal ability and nonlinear kernel transformation. Based on the ensemble connectivity prediction across the 72 models, we identified two major core areas, corresponding to the eastern and western portions of the central mountain range, significant attenuation of connectivity in lowland and developed areas of Panama, a major breakage in connectivity in the Canal Zone spanning the width of the country, and weak but potentially critical movement routes connecting the two core areas across the Canal Zone. This paper contributes to both a theoretical and practical understanding of the functional connectivity of large felids, confirming the strong effect of differences in source points and resistance surfaces on connectivity predictions and identifying and mapping key core areas, barriers, and potential corridors for carnivore movement across the critical Pan-American linkage of the Isthmus of Panama.